2020
DOI: 10.1016/j.pmip.2020.100066
|View full text |Cite
|
Sign up to set email alerts
|

Individualized theta-burst stimulation modulates hippocampal activity and connectivity in patients with major depressive disorder

Abstract: Background: While intermittent theta-burst stimulation (iTBS) has been shown to improve symptoms of major depressive disorder (MDD), research has been largely limited to targeting the dorsolateral prefrontal cortex (DLPFC). New approaches utilize patients' individual resting state fMRI data in order to identify superficial cortical stimulation targets functionally connected to deeper brain regions, thus enabling the modulation of previously inaccessible targets for antidepressant therapy. Objective: To improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…It should be noted that although a few multi-target rTMS studies have been reported ( Hendrikse et al. 2020 ; Mielacher et al. 2020 ), these studies involved stimulation of different effective regions.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that although a few multi-target rTMS studies have been reported ( Hendrikse et al. 2020 ; Mielacher et al. 2020 ), these studies involved stimulation of different effective regions.…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend is observed in humans, where theta-patterned electrical stimulation of the hippocampus or its inputs promotes memory specificity and paired associates learning (Jun et al, 2020;Titiz et al, 2017). While current TMS protocols cannot directly stimulate the human hippocampus, delivering theta-patterned TMS to parietal regions that are functionally connected to the hippocampus improves associative memory and hippocampal-cortical functional connectivity (Y.-C. Chen et al, 2022;Hermiller et al, 2020;Mielacher et al, 2020;Tambini et al, 2018).…”
Section: Introductionmentioning
confidence: 57%
“…While current TMS protocols cannot directly stimulate the human hippocampus, delivering theta‐patterned TMS to parietal regions that are functionally connected to the hippocampus improves associative memory and hippocampal–cortical functional connectivity (Y.‐C. Chen et al, 2022; Hermiller et al, 2020; Mielacher et al, 2020; Tambini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients with major depression who received iTBS to DLPFC in conjunction with parietal stimulation augmentation demonstrated increased functional connectivity between hippocampus and DLPFC, increased hippocampal response, and a stronger correlation between hippocampal response and cognitive function relative to patients receiving DLPFC stimulation only (Mielacher et al. 2020 ). These findings suggest that in order to optimise modulation of hippocampal cognitive/memory functions, future iTBS studies in bipolar disorder should target these parietal cortical regions.…”
Section: Discussionmentioning
confidence: 99%